Contamination by oil crude extraction – Refinement and their effects on human health. (December 2017) - Ramirez, Maria Isabel; Arevalo, Ana Paulina; Sotomayor, Santiago; Bailon-Moscoso, Natalia
Abstract: The harmful effects of oil on various species of flora and fauna have been studied extensively; however, few studies have studied the effects of oil exposure on human health. The objective of this research was to collect information on the acute health effects and serious psychological symptoms of the possible consequences of such exposure to crude oil. Some studies focused on the composition of different chemicals used in the extraction process, and wastes generated proved to be highly harmful to human health. Thus, studies have shown that individuals who live near oil fields or wells – or who take part in activities of cleaning oil spills – have presented health conditions, such as irritation to the skin, eyes, mucous membranes, kidney damage, liver, reproductive, among others. In Ecuador, this reality is not different from other countries, and some studies have shown increased diseases related with oil crude and oil spills, like skin irritation, throat, liver, lung, infertility, and abortions, and it has been linked to childhood leukemia. Other studies suggest a direct relationship between DNA damage because of oil resulting in a genetic instability of the main enzymes of cellular metabolism as well as a relationship with some cancers, such as leukemia. Graphical abstract: Highlights: Investigate in the literature on the effects of oil exposure on human health. Review effects of oil crude on health, this range from irritation throat to more serious illnesses as cancer. Review information on the effects caused by oil crude oil in the Amazon populations.